The mechanism of carbon–silica dual phase filler modified by ionic liquid and its reinforcing on natural rubber. Issue 9 (28th May 2014) - Wang, Jingyi; Jia, Hongbing; Ding, Lifeng; Xiong, Xin; Gong, Xuedong
<x xml:space="preserve">Abstract</x> The carbon–silica dual phase filler (CSDPF) was modified by ionic liquids (ILs): 1‐allyl‐3‐methyl‐imidazolium chloride (AMI) and 1‐butlyl‐3‐methyl‐imidazolium hexafluorophosphate (BMI). The modified CSDPF was then incorporated into natural rubber (NR) through mechanical mixing. The interactions between CSDPF and ILs were investigated using differential scanning calorimetry (DSC), Fourier‐transform infrared spectroscopy (FTIR), and Raman spectroscopy. The bound rubber of NR compounds, the mechanical properties, and dynamic properties of NR vulcanizates filled with ILs modified CSDPF (ILs‐CSDPF/NR) were measured. The results showed that the AMI interacted with CSDPF through both hydrogen bonds and van der Waals forces, while the interaction between BMI and CSDPF was merely weak van der Waals force. The modification of CSDPF by ILs could improve the tensile strength, tear resistance, and fatigue life of NR vulcanizates. The AMI‐CSDPF/NR gave the superior mechanical and dynamic properties among the NR vulcanizates with the highest bound rubber content and the most homogeneous filler dispersion, which was displayed in scanning electron microscope (SEM) images. POLYM. COMPOS., 36:1721–1730, 2015. © 2014 Society of Plastics Engineers